The discourse of televised political news interviews and ethnic polarization in Kenya - Omoke, Lillian Kemunto (UoeM, 2017)
Political interviews have been used as genres for dissemination of political information. The way they are presented is a subject of concern as they are thought to be causing division among the Kenyan audience along political party and hence ethnic lines. The purpose of this study is to look at the discursive practices in political news interviews and the interpretation they are given by the audience that may lead to ethnic polarization. The main objective of this study was to analyze the influence of televised political news interviews on ethnic polarization in Kenya. Two theories were used to support this study: Theory of Media Framing and Critical Discourse Analysis. The fusion of these approaches was helpful in showing how messages are selected and packaged and the ideological influences they have. The study adopted a qualitative design. A total of 6 recorded televised interviews were studied, two from Citizen TV and one from each the other stations samples (KTN, NTV, K24, KBC). Data collection and analysis was simultaneously done by transcribing the political news interviews and interpreting them using the Critical Discourse Analysis approach. Other data collection methods such as in-depth interviews, focus group discussions and document analysis were employed. Data presentation was done through discussing the interpretation against the institutional, societal, historical and political contexts in which the interviews were conducted. The findings showed that linguistic features are used subtly to cause polarization and it was established that the naming and referencing strategy was commonly used to create an US vs THEM mentality among audiences hence polarization. It was also established that the media treat audiences as markets and products hence presenting sensational news to attract ratings and eventually profits. It was concluded that political news interviews actually lead to ethnic polarization based on the production processes, language use, and ideological stands and through the use of media frames. The key recommendation from the study was that there should be audience awareness programmes on the processes and operations of the media.
Thesis